2011
DOI: 10.1016/j.neurobiolaging.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and hippocampal volume in women at risk for Alzheimer's disease

Abstract: Insulin resistance (IR) is the main pathological condition underlying vascular disorders, such as diabetes and cardiovascular disease, which are well established risk factors for cognitive decline and Alzheimer disease (AD). Hippocampal atrophy has been associated with cognitive decline, but little is known about the influence of IR on hippocampus integrity in non-diabetic, cognitivelyintact individuals. Herein, 50 women ages 50-65, current users of hormone therapy, underwent magnetic resonance imaging, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 37 publications
10
107
0
1
Order By: Relevance
“…Findings were similar to those of the current study, in that results were not solely attributable to possession of the APOEe4 allele. 17,19,21 This similarity further supports our assertion that factors associated with glucose control may impart an independent contribution to AD risk.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Findings were similar to those of the current study, in that results were not solely attributable to possession of the APOEe4 allele. 17,19,21 This similarity further supports our assertion that factors associated with glucose control may impart an independent contribution to AD risk.…”
supporting
confidence: 85%
“…17 Other structural MRI studies of AD risk have also demonstrated that higher levels of insulin resistance have been associated with increased total cerebral brain atrophy 20 and lower right and total hippocampal volume. 21 Furthermore, select studies also considered the genetic contribution to imaging outcomes. Findings were similar to those of the current study, in that results were not solely attributable to possession of the APOEe4 allele.…”
mentioning
confidence: 99%
“…Consequently, participants with type 2 diabetes mellitus (T2DM) typically display smaller hippocampal volumes than nondiabetic controls (den Heijer et al, 2003;Gold et al, 2007;Bruehl et al, 2009;Wrighten et al, 2009;Brundel et al, 2010;Hayashi et al, 2011). The hippocampal volume alterations may occur already in participants with impaired glucose tolerance (Convit et al, 2003) or insulin resistance (IR, Rasgon et al, 2011;Willette et al, 2013). The brain changes in T2DM or IR may not be isolated to the hippocampus, as suggested by some studies (Gold et al, 2007;Bruehl et al, 2009;Brundel et al, 2010;Rasgon et al, 2011;Willette et al, 2013), but may extend into cortical regions (Benedict et al, 2012;Moran et al, 2013;Willette et al, 2013;Garcia-Casares et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that brain aging is associated with a decrease of central insulin concentration [64][65][66], with an impairment of insulin receptor binding ability, resulting in an increase in deterioration of glucose homeostasis in the brain. Brain insulin resistance [67] is associated to peripheral insulin resistance-a typical feature of elder ages, associated to atherogenic dyslipidemia [65], and ET influences insulin resistance in medial prefrontal gyrus metabolism.…”
Section: Hypothesis On Brain Aging and Neurodegeneration During Perimmentioning
confidence: 99%